4′‐Phosphopantetheine corrects CoA, iron, and dopamine metabolic defects in mammalian models of PKAN. Issue 12 (29th October 2019) - Jeong, Suh Young; Hogarth, Penelope; Placzek, Andrew; Gregory, Allison M; Fox, Rachel; Zhen, Dolly; Hamada, Jeffrey; van der Zwaag, Marianne; Lambrechts, Roald; Jin, Haihong; Nilsen, Aaron; Cobb, Jared; et al.
Abstract: Pantothenate kinase‐associated neurodegeneration (PKAN) is an inborn error of CoA metabolism causing dystonia, parkinsonism, and brain iron accumulation. Lack of a good mammalian model has impeded studies of pathogenesis and development of rational therapeutics. We took a new approach to investigating an existing mouse mutant of Pank2 and found that isolating the disease‐vulnerable brain revealed regional perturbations in CoA metabolism, iron homeostasis, and dopamine metabolism and functional defects in complex I and pyruvate dehydrogenase. Feeding mice a CoA pathway intermediate, 4′‐phosphopantetheine, normalized levels of the CoA‐, iron‐, and dopamine‐related biomarkers as well as activities of mitochondrial enzymes. Human cell changes also were recovered by 4′‐phosphopantetheine. We can mechanistically link a defect in CoA metabolism to these secondary effects via the activation of mitochondrial acyl carrier protein, which is essential to oxidative phosphorylation, iron–sulfur cluster biogenesis, and mitochondrial fatty acid synthesis. We demonstrate the fidelity of our model in recapitulating features of the human disease. Moreover, we identify pharmacodynamic biomarkers, provide insights into disease pathogenesis, and offer evidence for 4′‐phosphopantetheine as a candidate therapeutic for PKAN. Synopsis: Mutations in PANK2 cause pantothenate kinase‐associated neurodegeneration (PKAN), a neurodegeneration with brain iron accumulation (NBIA) disorder. This study presents a mouse model that recapitulates key features of the human disease and shows rescue by a coenzyme A pathway intermediate. Germline deletion of Pank2, encoding pantothenate kinase 2, causes defects in CoA, iron, and dopamine metabolism and diminished activities of mitochondrial aconitase, complex I, and pyruvate dehydrogenase (PDH) in globus pallidus. Regional biomarker abnormalities, which are revealed by isolating disease‐vulnerable brain regions, are specifically attributable to a defect in Pank2 alone, without the need to superimpose further genetic or metabolic defects. Correction of the CoA metabolic defect by oral administration of 4′‐phosphopantetheine recovers iron and dopamine homeostasis in brain and normalizes mitochondrial complex I and PDH activities. Abstract : Mutations in PANK2 cause pantothenate kinase‐associated neurodegeneration (PKAN), a neurodegeneration with brain iron accumulation (NBIA) disorder. This study presents a mouse model that recapitulates key features of the human disease and shows rescue by a coenzyme A pathway intermediate.